The Joy Luck Club - Tan, Amy. (New York : Putnam's, 1989)
In 1949, four Chinese women begin meeting in San Francisco to play mah jong, invest in stocks, eat dim sum and "say" stories. They call their gathering the Joy Luck Club.
A novel.
930
Keywords: Chinese Americans -- Fiction; Mothers and daughters -- United States -- Fiction